Temperature elevation investigations on the external root surface during irradiation with 940 nm diode laser in root canal treatment - Sheima'a A Al-Zand; Mohammed A Al-Maliky; Ali S Mahmood; Tamara S Al-Karadaghy (Wolters Kluwer Medknow Publications, 2018)
Background: The root canal system is complex. Eliminating the microorganisms from it is not easy. Diode laser is proposed as one of the effective methods to sterilize the canal. Aims: The aim of this work was to evaluate the diode laser parameters to be used as an adjunct for root canal sterilization to avoid any increase in temperature to prevent any thermal collateral damage to the periodontal tissue. Materials and Methods: A total of 24 single-canal premolars were used; they were divided randomly into two groups (n = 12). Group 1 was irradiated with 1.5 W continuous wave mode of diode laser and Group 2 with 2.5 W/2 5 Hz pulsed mode of the diode laser. The temperature was measured using thermometer and thermal camera at the apical part of the root. Post hoc test, Student's t-test, and paired t-test were used in the study. Results: The results showed a modest increase in temperature at the external root surface for Group 1, with maximum increase of 6.7°C in apical portion, and 8.5°C for Group 2. Conclusions: Within the present parameters, the laser is safe for use as an adjunct for root canal sterilization.